Estetica e poetica in Giovan Battista Gelli Gli scritti sull'arte e su Dante - Pini, Carolina (Classicism and Beyond / Il classicismo e oltre, 2023)
This volume studies the profile of one of the most important figures of 16th-century Florence, Giovan Battista Gelli, highlighting some less studied aspects: not only was Gelli deeply interested in figurative art, attested in several works of his, he can also be considered one of the protagonists of the vivid debates on Dante.